PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP PENINGKATAN AKHLAK SISWA (Studi Survei di SMA Diponegoro 2 Jakarta) - Rizka Fajriah Anwar; Maria Ulfah; Kunaenih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research sets out to examine how far Islamic Religious Education (IRE) contributes to strengthening the moral conduct of students at SMA Diponegoro 2 Jakarta. It was prompted by an observable gap between the values conveyed in IRE classes and students' actual day-to-day behavior, including weak discipline, limited respect toward teachers, and recurring cheating. A quantitative, descriptive-analytical method was adopted, employing a cross-sectional design. Out of a population of 301 students, 75 respondents were selected through purposive sampling with the Slovin formula. Data collection combined a comprehension test on Fiqh of Worship to gauge the IRE variable (X) with a Likert-scale questionnaire to assess the Student Morals variable (Y), further supported by observation, interviews, and documentation. The Product Moment correlation technique was used for data analysis, yielding a correlation coefficient (rxy) of 0.415 a value that surpasses the r-table figures at both the 5% (0.227) and 1% (0.296) significance levels, leading to acceptance of the Alternative Hypothesis (Ha). The coefficient of determination (R Square) of 0.172 reveals that IRE accounts for 17.2% of the improvement in students' morals, while the remaining 82.8% stems from other factors such as family environment, peer relationships, and social media exposure. Overall, the findings point to a positive and significant relationship, falling within the moderate category, between IRE and the enhancement of students' morals at SMA Diponegoro 2 Jakarta. Keywords: Islamic Religious Education, Student Morals, Product Moment Correlation